PARP-1: a critical regulator in radioprotection and radiotherapy-mechanisms, challenges, and therapeutic opportunities - Li, Wen-Hao; Wang, Fei; Song, Gui-Yuan; Yu, Qing-Hua; Du, Rui-Peng; Xu, Ping (Frontiers in Pharmacology, 2023)
Background: Since its discovery, PARP-1 has been extensively characterized as a regulator of numerous biologically important pathways. PARP inhibitors provide new therapeutic opportunities to cancer patients, leading to their approval as single-agent treatments for certain cancer types. The further advancement of the PARP inhibitor research space has the potential to fully realize the value of targeting this pathway as a treatment for many different diseases. Purpose: To assess the current state of PARP in the literature regarding mechanism in radiaoprotection and radiotherapy. Methods:We searched the pubmed database and summarized PARP inhibitors, PARP-1 and DNA, PARP-1 and p53/ROS, PARP-1 and NF-κB/DNA-PK and PARP-1 and caspase3/AIF. Results: The enzyme poly (ADP-ribose) polymerase 1 (PARP-1) is responsible for the repair of DNA damage and protein modification. DNA damage can occur when cells are exposed to radiation and single-, intra-, or inter-strand damage associated with replication fork stagnation leads to the activation of the DNA repair mechanism, including PARP-1. The activity of PARP-1 increases 500-fold on DNA binding. Studies on PARP-1-knockdown mice have shown that the protein regulates the response to radiation. A lack of PARP-1 also increases the sensitivity of the organism to radiation injury. PARP-1 has been found positively or negatively regulate the expression of specific genes through its modulation of key transcription factors and other molecules, including NF-κB, p53, Caspase 3, ROS, and apoptosis-inducing factor (AIF). Conclusions:The present review presents a comprehensive discussion of the physiological and pathological roles of PARP-1, together with the effects of PARP-1 inhibitors in the context of ionizing radiation exposure. The review also emphasizes the challenges and opportunities for the development of PARP-1 inhibitors aimed at improving the clinical outcomes of ionizing radiation damage.